2022
DOI: 10.1111/ddi.13472
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal patterns of emergence phenology reveal complex species‐specific responses to temperature in aquatic insects

Abstract: Aim: Climate change is broadly affecting phenology, but species-specific phenological response to temperature is not well understood. In streams, insect emergence has important ecosystem-level consequences because emergent adults link aquatic and terrestrial food webs. We quantified emergence timing and duration (within-population synchronicity) of insects among streams along a spatiotemporal gradient of mean water temperature in a montane basin to assess the sensitivity of these phenological traits to heat ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 118 publications
(150 reference statements)
0
12
0
Order By: Relevance
“…But it emphasizes the limits of degree day estimates when calculated as annual sums, rather than incremental values that can be matched to specific Julian dates. Incremental or cumulative degree day values could be aligned directly with emergence dates, providing a mechanistic link to emergence (Cayton et al, 2015; Finn et al, 2022); this approach would be more powerful than the correlative one used here for DD18 and DOY. Similarly, degree days from the prior year may improve emergence timing models, particularly for semivoltine taxa (Richter et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…But it emphasizes the limits of degree day estimates when calculated as annual sums, rather than incremental values that can be matched to specific Julian dates. Incremental or cumulative degree day values could be aligned directly with emergence dates, providing a mechanistic link to emergence (Cayton et al, 2015; Finn et al, 2022); this approach would be more powerful than the correlative one used here for DD18 and DOY. Similarly, degree days from the prior year may improve emergence timing models, particularly for semivoltine taxa (Richter et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This caddisfly occurs in high densities during the flowing phase in Shelton Creek and has been documented to have egg diapause (Bowles & Allen, 1992). It is possible that caddisflies and other taxa underrepresented in our buckets have dormant stages that develop in response to additional cues beyond the presence of water (e.g., temperature; Finn et al, 2022).…”
Section: Figurementioning
confidence: 99%
“…Our special issue contributes to the field by identifying key linkages between physiological and other traits. Finn et al (2022) assessed the sensitivity of phenological traits (emergence timing and duration) to heat accumulation (i.e. cumulative degree‐days) of the four most abundant, spring‐emerging species from the orders Ephemeroptera, Plecoptera, and Trichoptera during the emergence period in six headwater streams with different elevation in the Lookout Creek basin, Oregon.…”
Section: Section A: Species Sensitivity/resiliencementioning
confidence: 99%
“…The authors also observed highly variable phenological responses among different populations and species, indicating three clearly different phenological patterns with different thermal regimes among four aquatic insect species. Finn et al (2022) hypothesized a trade‐off between a complex phenological response that synchronizes emergence among heterogeneous sites and other traits such as adult longevity and dispersal capacity. This work sheds new light on the complexity of phenological responses of aquatic insects to water temperature and climate change and indicates key directions for future research.…”
Section: Section A: Species Sensitivity/resiliencementioning
confidence: 99%